Petrogenesis of silica-rich carbonatites from continental rift settings: a missing link between carbonatites and carbonated silicate melts? - Ackerman,L.; Rapprich,V.; Polak,L.; Magna,T.; Mclemore,V.T.; Pour,O.; Cejkova,B. (Journal of Geosciences, 2021)
Four carbonatite bodies (Sukulu and Tororo - Uganda, Lemitar and Iron Hill - USA) from two intracontinental rift systems containing a prominent silicocarbonatite-carbonatite association were studied in detail in terms of petrography, major-/trace-element chemistry, and Sr-Nd-C-O isotope systematics to provide constraints on their petrogenesis and mutual relationship. The Sukulu and Tororo carbonatites (< 30 Ma) within the East African Rift System are characterized by the wide range of SiO2 contents and presence of phlogopite ± olivine and aegirine-augite + K-feldspar, respectively. These different mineral parageneses correspond to the Mg-K-rich nature of the former and Na-Fe-K-rich composition of the latter. Overall, these signatures can explained at best by the progressive fractionation of parental carbonated silicate melts and liquid immiscibility documented by the chemical variation of clinopyroxene and the presence of silicate-carbonate pockets. However, at Tororo, this process was likely accompanied by assimilation of local crustal lithologies to account for its different Sr-Nd isotopic signatures and Na-rich nature of carbonatites. Despite their spatial and temporal difference, the Lemitar and Iron Hill from the Cambro-Ordovician North American Rift resemble similar petrography and mineralogy as Sukulu and Tororo bodies expressed by the presence of phlogopite and clinopyroxene + K-feldspar, respectively. We present a general model explaining the origin of silicocarbonatite-carbonatite association involving segregation of silicate and carbonate melts from parental carbonated silicate melts through a process of liquid immiscibility. Subsequent distinct evolutionary paths are related to differences in Si-Na-K-Fe-Mg and H2O-F contents, oxygen fugacity, and melt ascent efficiency, perhaps related to crustal assimilation. Therefore, we emphasize that relatively silica-rich carbonatites represent a crucial linkage between silicate and carbonate melts.
Keywords: carbonatite; silicate melt; rift system; Sr-Nd isotopes; C-O isotopes